What Constitutes "Complement" in Systemic Functional Grammar: Its Theoretical Problems and Implications - Kusmanto, Joko (PRASASTI: Journal of Linguistics, 2013)
Despite the wide-range application of Systemic Functional Grammar (SFG) for various kinds of text analyses, SFG theory poses significant syntactic problems which have not been touched much. These syntactic problems are basically the result of its fundamental theoretical construct, i.e. the semantic perspective in approaching grammar. In fact, this theoretical construct seems to mix up the syntactic function and the semantic role analysis, two out three levels in syntactic analysis. It results in a serious inconsistency in labeling the syntactic unit of analysis in a clause and in defining many terms as well. This paper roughly explores both syntactic and semantic problems which appear in Mood system, particularly the label ‘Complement’. This paper does not discuss each problem in detail and in a systematic way; rather it will only show us that there are still many works to do in the theory of SFG itself. Thus, there should be more scholars and advocates of this school of grammar focusing their investigations on the theoretical level of grammatical/syntactic issues.